EFEKTIFITAS METODE PENGOLAHAN KULIT PISANG (Musa paradisiaca) TERHADAP KECERNAAN NUTRIEN AYAM KAMPUNG FASE GROWER (Effect of Different Feed Procession Method of Banana Peel (Musa paradisiaca) on Grower Phase Native Chicken Feed Digestibility) - H. Has; Amiluddin Indi; W. Kurniawan; A. Pagala (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
Banana peel (Musa paradisiaca) was banana processing waste with high availability but low utility as poultry feed. Utilization peel of banana as poultry feed required special processing methods to increase digestibility. This research was aimed to evaluate nutrient digestibility of banana peel with different processing methods on native chicken. Twenty birds native chicken aged 10 weeks with 600 g average body weight, banana peel, NaOH, tempeh yeast (Rhyzopus sp), bacterial starter (EM4) were used as research materials. The experimental design was completely randomized design (CRD) four treatments and fve replications: T0 (control: without treatment), T1 (banana peel soaked 10% NaOH), T2 (banana peel fermented by tempeh yeast), T3 (banana peel fermented by EM4). Parameters measured were digestibility of nutrients: dry matter digestibility (DMD), organic matter digestibility (OMD), and Crude Protein Digestibility (CPD). Obtained data were analyzed using SPSS software version 2.0., the signifcant different were tested by Duncan Multiple Range Test (DMRT). Research results showed that the effect of different processeing methods of banana peel were signifcantly (P <0.05) on DMD, OMD and CPD. This research concluded that banana peel fermented by EM4 treatment have higher DMD, OMD and CPD compare than others.